(untitled) (Fiep Bulletin - online, 2011)
The Down’s syndrome, which presents itself as a chromosomepathy characterized by the additional presence of a chromosome in the 21st pair, causes a disturbance to the human body cell functions, making people who have this alteration present injure in their organic system and, thus, bigger sensitivity to some illnesses. Facing this problem, in this project, in which a method of a context assessment was used, the objective was to develop an assessment concerning the breathing profile in 4-to-10-year-old children who bear the Down’s syndrome and live in Gurupi/TO. This research paper was submitted to the Research Ethics Committee involving Human Beings of the Castelo Branco University (Rio de Janeiro/Brazil) and approved under the protocol # 0167/2008. The data collection was done according to the resolution 196/96. The results evidenced that the group presents, predominantly, mouth breathing. Through the meaningful Test t, it was statistically proved that these people perform mouth breathing. It’s concluded that they have a decrease of strength on the facial muscles because of an inherent hypotonicity. This makes it difficult for them to keep an appropriate nose breathing. Thus, the risk of breathing infections increase and this can lead them to death. Due to this, it’s vital to have a physiotherapeutic intervention to have the strength and muscle system function back, especially the segments involved in breathing.